2018
DOI: 10.1111/papt.12179
|View full text |Cite
|
Sign up to set email alerts
|

Mentalization‐based treatment or psychodynamic treatment programmes for patients with borderline personality disorder – the impact of clinical severity

Abstract: Objectives. Mentalization-based treatment (MBT), originally designed for patients with borderline personality disorder (BPD), may be particularly indicated for severe conditions. However, there is limited documentation of how increasing severity of personality disorder (PD) effect outcomes of highly specialized treatments. This study aimed to investigate associations between clinical severity and outcomes for patients in MBT as compared to a psychodynamic group-based treatment programme (PDT).Design. A natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…In 2013-2015, five raters evaluated 19 individual sessions (eight therapists) and 9 group sessions in the programme. For individual therapists, the mean adherence level was 4.7 (SD = 1.2) and the mean MBT competence level was 4.4 (SD = 1.2) (Kvarstein et al, 2019). For group therapists, the mean adherence level was 5.1 (SD = 1.37) and competence level 4.9 (SD = 1.30) (Kvarstein et al, 2020).…”
Section: Therapist Mbt Fidelitymentioning
confidence: 95%
See 1 more Smart Citation
“…In 2013-2015, five raters evaluated 19 individual sessions (eight therapists) and 9 group sessions in the programme. For individual therapists, the mean adherence level was 4.7 (SD = 1.2) and the mean MBT competence level was 4.4 (SD = 1.2) (Kvarstein et al, 2019). For group therapists, the mean adherence level was 5.1 (SD = 1.37) and competence level 4.9 (SD = 1.30) (Kvarstein et al, 2020).…”
Section: Therapist Mbt Fidelitymentioning
confidence: 95%
“…However, the clinical severity of PD in terms of comorbidity has been investigated. Studies of social cognition among patients with BPD have indicated that more impaired mentalizing is associated with more severe, comorbid PD (Normann-Eide et al, 2019), and MBT studies differentiating between patients with only BPD and patients with PD comorbidity recommend MBT for the more complex conditions (Kvarstein et al, 2019). BPD with comorbid paranoid PD represents a common form of severe personality pathology and can be conceptualized within the frame of epistemic trust.…”
Section: Main Findingsmentioning
confidence: 99%
“…In addition, the GSI was 1.54 (SD = 0.66) and IIP was 1.65 (SD = 0.52). With respect to GSI this score is in the "Moderate" to "Sever" range [37,42,43], and a score of 1.65 on CIP is associated with severe interpersonal distress [42,44]. Thus, all these measures reflect a poorly functioning patient group with a high level of symptom and interpersonal distress.…”
Section: Patientsmentioning
confidence: 99%
“…Keeping a therapeutic focus on mental states, interpersonal interpretation, and interaction, it provides an explicit challenge of mentalizing others, both therapists and group members. MBT studies have indicated that this specialized approach is particularly justified for BPD patients with severe disorder ( 20 22 ). For patients, the treatment, interventions, and formats, represent complex social situations and will activate all aspects of social cognition.…”
Section: Introductionmentioning
confidence: 99%